A SDGs-oriented evaluation of the ecological sustainability of international horticultural exposition sites in Chengdu, China - Huang, Biao; Yang, Haolin; Shang, Kankan; Wang, Ruoyu; Meng, Yufei; Peng, Hongming; Hu, Yonghong; Jiang, Zehui (Journal of Environmental Engineering and Landscape Management, 2025)
This study employs the AHP-entropy weight methodology and a spatial econometric regression model to evaluate the ecological sustainability and its changes between the current situation and the planning scenario at the 2024 Chengdu International Horticultural Exposition in China. The results indicate a notable shift: a reduction in areas of low and highest sustainability and significant expansion in medium levels, which spans 34.04 hm2. The transformation of village settlements, wastelands, and farmland into exhibition gardens and water bodies is shown to bolster medium-level ecological sustainability by enhancing rain and flood security and mitigating the risk of flood disasters. The development of Integrated Service areas will lead to an increase in impervious surfaces. The anticipated forest loss, along with declines in vegetation coverage, three-dimensional green volume, and vegetation carbon stock will adversely affect the highest sustainability. The study identifies a robust correlation between ecological sustainability level and quantitative indicators, with regression coefficients ranging from 0.5875 to 0.7148. This analysis provides policymakers with valuable insights and directions for the sustainable planning and development of mega-events.